The decision to enrol in higher education - Dominik Hügle (Freie Universität Berlin, School of Business & Economics, 2021)
In this paper, I analyze how the higher education decision of young adults in Germany depends on their expected future earnings. For this, I estimate a microeconometric model in which individuals maximize life-time utility by choosing whether or not to enter higher education. To forecast individual life cycles in terms of employment, earnings, and family formation under higher education and its alternative, vocational training, I use a dynamic microsimulation model and regression techniques. I take into account that while individuals generally choose between two options, higher education and vocational training, they are aware of multiple potential realizations under both options, such as leaving higher education with a bachelor degree or taking up higher education after first having earned a vocational degree. Using the estimates from the decision model, I simulate the introduction of different tuition fee and graduate tax scenarios. I find that the impact of these education policies on the higher education decision is limited and only few individuals would change their educational decisions as a reaction to these policies.
urn:nbn:de:kobv:188-refubium-30206-5
Keywords: C53; I23; 330; Educational choice; Higher education; Dynamic microsimulation